Digital drivers of digital transformation in public sector organizations - Mohammad Faleh Hunitie; Abdel Hakim Akhorshaideh (International Journal of Data and Network Science)
This study aimed to investigate digital drivers of digital transformation success in public sector organizations. Based on prior related studies, three digital drivers were selected as key drivers, which are digital government, digital leadership, and digital HRM. Gathering data by online questionnaires from public sector employees, the study based on SmartPLS 3.0 statistics found significant and positive impacts of these three drivers on digital transformation success. Interestingly, the results refer to the success of digital transformation is greatly subject to digital HRM and possibly this effect is due to the fact that the basic aim of digital government and digital leadership is to enhance the operations of the digitization process through adopting digital-oriented public administration mentality, creating public value, setting shared digital vision and strategy, communicating digital change goals, initiating digital organizational culture, which is basically guided and can be attained through efficient and effective digital HRM practices. Hence, the study contributes to the literature through underlying three digital drivers of digital transformation success. It calls scholars for considering these drivers when examining success factors of digital transformation and practitioners when redesigning organizations to adapt digital change.